Acute complications of preeclampsia: prognosis and management at Pikine National Hospital in Dakar (Senegal) - M., Diallo; A. A., Diouf; A. C., Niassy; C. E. G., Gombet; Lydie, D.; A., Niass; O., Gassama; M. D. N., Gueye; M., Gueye; M. M., Niang; S., Coulbary; A., Diouf (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
ABSTRACT Background: The objective of this study was to evaluate the prevalence of acute complications of preeclampsia in order to describe the epidemiological profile of the disease, to assess its prognosis and management. Methods: This was a retrospective study of patients admitted to the Pikine National Hospital from 1 January 2010 to 31 December 2013 (48 months) with severe complicated pre-eclampsia. Included in this study were patients admitted or diagnosed with severe complicated pre-eclampsia and having given birth in the structure or not. Results: The incidence of severe preeclampsia in childbirth varied from 9.7% to 11.5% during the four years of our study. Patients were largely paucigest (55.7% of cases) and paucipares (58.5% of cases). The mean age was 28.14 years with extremes of 14 and 47 years. More than half of the patients (57.7%) were between 21 and 34 years of age. They were mostly married (90.7%). Three-quarters of the patients (76.8%) had proteinuria with ≥ 3 cross-bands. Thrombocytopenia was found in 9.7% of patients, hepatic cytolysis in 12.1%, and elevation of serum creatinine in 13.8%. The level of transaminases was found to be greater than 2 in the normal range in 12.1%. Complicated forms were the most represented in our study. These were acute complications, with 715 cases, or 57.3% of the patients. They were either isolated (52.8%) or associated (4.5%). These included eclampsia (24.9%), followed by retroplacental hematoma (24.6%), fetal death in utero (23.7%), HELLP syndrome (3.4%). , Acute edema of the lungs (1.5%), and acute renal failure (1.4%). The lethality was 2.4%. The causes of maternal death were dominated by eclampsia (14 cases), DIC (3 cases) and OAP (2 cases). We counted 77.7% of live births and a stillbirth of 254.5 ‰. Conclusions: Pre-eclampsia is a serious complication of pregnancy. Its frequency is still high in sub-Saharan Africa. In the presence of signs of severity, maternal (vital and functional) and neonatal prognosis are inevitably involved. If management is based on fetal extraction, resuscitation measures are a guarantee of maternal survival.